Effect of deep frying temperatures in some of quality characteristics of French fries (var. S.Sponta) and Sunflower Oil (Journal of Hama University, 2024)
This study aimed to investigate the effect of frying temperature (165, 175, 185°C) on some of quality characteristics of French fries (moisture content, fat content, color indices), determine optimal frying conditions, in addition to estimate the acrylamide content in the samples. The chemical indicators of sunflower oil at the end of the traditional frying process of French fries, and the maximum number of frying hours were determined also.Results showed that temperatures is one of the main factors that affect the frying quality of French fries, and that the optimum temperature for the frying process is 175 °C, at which the moisture content is 31.52%, and the absorbed oil content is 26.11%, for the values of the color indices, the brightness L* were 66.37, the redness index a* was 5.31, and the yellowness index b* was 30.62, while the color difference ∆E was 11.47, and the browning index BI was 65.95. The sensory properties of fried samples results were 7.8, 7.6, 7.8, and 8.4 for the tests of general acceptance, color, flavor, and texture, respectively, while the percentage of acrylamide reached 902.64 g/kg, in account to daily replenishment by loss ratio.